2013
DOI: 10.1039/c3fd00066d
|View full text |Cite
|
Sign up to set email alerts
|

Population and size distribution of solute-rich mesospecies within mesostructured aqueous amino acid solutions

Abstract: Aqueous solutions of highly soluble substances such as small amino acids are usually assumed to be essentially homogenous systems with some degree of short range local structuring due to specific interactions on the sub-nanometre scale (e.g. molecular clusters, hydration shells), usually not exceeding several solute molecules. However, recent theoretical and experimental studies have indicated the presence of much larger supramolecular assemblies or mesospecies in solutions of small organic and inorganic molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
104
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(116 citation statements)
references
References 59 publications
(79 reference statements)
12
104
0
Order By: Relevance
“…We choose glycine because it is a well studied model system for studies of nucleation of crystals from solution 2,3,6,10,12,13,[16][17][18][19][20][21][22][23][24][25][26][27][28] . Glycine has three polymorphs: α, γ and β. α glycine is the most common polymorph to crystallise from aqueous solution at neutral pH, but the γ polymorph is the most stable of the glycine polymorphs 29 .…”
Section: A Previous Work On Glycinementioning
confidence: 99%
“…We choose glycine because it is a well studied model system for studies of nucleation of crystals from solution 2,3,6,10,12,13,[16][17][18][19][20][21][22][23][24][25][26][27][28] . Glycine has three polymorphs: α, γ and β. α glycine is the most common polymorph to crystallise from aqueous solution at neutral pH, but the γ polymorph is the most stable of the glycine polymorphs 29 .…”
Section: A Previous Work On Glycinementioning
confidence: 99%
“…20 Now, while the γ polymorph can be obtained, [4][5][6][7]11,12,14 the α polymorph is generally found on crystallisation from aqueous solution at neutral pH. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] Glycine's solubility is very sensitive to temperature, 21 making it easy experimentally to vary the supersaturation. The α polymorph has a very fast growth rate (radial growth rates on the order of 1 mm/s have been observed 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is an ideal model system that has been studied extensively in earlier work. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Glycine is an easy-to-work-with molecule, which forms three polymorphs: α, γ and β . The γ polymorph is the most stable of the glycine polymorphs.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study of undersaturated and supersaturated aqueous solution of DL-alanine revealed that mesoscale clusters with the size range from 100 to 300nm exist well below solid-liquid equilibrium concentration (saturation 30 limit). It has been concluded that the mesoscale clusters are not a separate phase and the system has been described as a thermodynamically stable mesostructured liquid containing solute-rich domains dispersed within bulk solution 43 . We have previously reported presence of submicron size 35 mesospecies in supersaturated aqueous glycine solutions and their likely role in nucleation of glycine crystals 44 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the distribution of valine, water and 2-propanol between the 45 mesoscale clusters and surrounding solution may be fixed at any particular composition and temperature but continuously variable as the total composition or temperature is changed. This provides a possible reason for why the mesostructured liquid is the most thermodynamically stable phase from the point at which 50 monomers or small molecular cluster assemble to mesoscale clusters (critical mesoscale cluster concentration) 43 up to the composition where the crystalline phase becomes stable (solubility). At higher concentration the mesostructured liquid phase will continue to be the most kinetically accessible phase 55 but since it is supersaturated it will be metastable with respect to the solid phase.…”
mentioning
confidence: 99%